John Wain: a writers life and work - Elizabeth Hatziolou (1996)
This thesis is intended to serve two purposes. On the one hand, it aims to present the story of John Wain's life and on the other to offer an analysis and assessment of his novels, short stories, poetry, drama, criticism and editorship. The opening chapter deals mainly with the facts of the writer's early years and tells of personal experiences which may be thought responsible for the formation of his ideas and beliefs. The next chapter looks at his undergraduate years at Oxford and presents a picture of his tutors and the friendships he there made, some of which would last a lifetime. It also deals with his interests and developing attitude to life. Chapter three considers John Wain's contributions to Mandrake, the literary magazine he founded at Oxford, and assesses his first poetry collection, Mixed Feelings, which launched him into the contemporary literary world. It also looks at John Wain's academic career and discusses Preliminary Essays, a work which established him as a lively, controversial critic and an important spokesman for values that came to be identified with 'The Movement'. Attention is also paid to his first marriage and personal life. Chapter four offers a survey of his literary radio programmes First Reading and examines reasons why the series aroused the interest of the public and the press. It analyses and assesses John Wain's first and second novels and describes how he came to resign from his academic post and obtain a legal dissolution of his marriage. The following chapter discusses the novels, short stories, poetry, drama and criticism wain wrote in the sixties and seeks to present his evolution as novelist, poet and critic. Chapter five also discusses his second marriage, describes his life in London and friendships with fellow writers, and relates his attempt to become a playwright. Chapter six is an assessment of the work he produced in the seventies as well as an analysis of his lectures and the preoccupation that emerged in the lectures he gave as Professor of Poetry at Oxford. It considers his biography of Samuel Johnson and examines the reasons why Johnson mattered to him so much. The chapter finally discusses his plays Harry in the Night and You Wouldn't Remember. Chapter seven discusses the novels, short stories, poetry and criticism he wrote in the eighties as well as his autobiography Dear Shadows. It includes a discussion of his radio play Frank and concludes with an account of his financial worries. Chapter eight assesses the novels and plays he wrote in the nineties and provides details of his personal life. In particular it provides an account of his last days and the reaction of his friends and fellow academics to his death.